L’autre scène dans The Three Birds de Joanna Laurens (2000) : enjeux dramatiques de la réécriture d’un mythe - Solange Ayache (Sillages Critiques)
Joanna Laurens’ first play The Three Birds (2000) is a retelling of the Greek myth of Philomela in which language undergoes a poetic treatment unprecedented on the contemporary British stage. Mirroring and enacting the characters’ evolution from innocence to barbarism, language is distorted and altered to an extreme through a creative process involving word coinage (i.e. barbarisms), syntactic irregularities, and ‘babelisation,’ thus bringing out and performing the violence of the myth. Departing from Ovid’s poem which is itself a reworking of the original fable, as well as from the feminist takes on the story during the second half of the twentieth century, Laurens’ dramatic writing offers a new approach to the language and figure of the Barbarian, a traditional paradigm of the Other. She addresses such issues as the oppression of minorities, the voice of the stranger, and the reversibility of ethical positions by providing a reflection on the intrinsic duplicity of language itself and by exploring its potential for ‘metamorphosis’ and manipulation, thus presenting otherness as alienation. At the core of the play, which is a rewriting of another (lost) tragedy – that of Sophocles’ Tereus –, are Tereus’ lies, which are a rewriting of another (taboo) story – that of Philomela’s rape and amputated tongue. Although it can’t be verbally expressed by the young woman, this traumatic episode is nonetheless revealed through a tapestry she weaves for her sister Procné to denounce the crime of the lying husband, the needlework compensating her lost voice. This article thus looks at the issues at stake in Laurens’ rewriting, which can be read as the Other of the Greek myth and its famous feminist interpretations. Not only does her play propose an alternative which stems from an unusual, profoundly humane perspective – the suffering of a man whose love is thwarted – but this reversal is also mirrored in the intradiegetic motif of the tapestry as a writing of the Other (the scene behind the scenes, unheard of) by the Other (the abused, silenced woman). I propose to study how the Other comes to be inscribed at the core of language where it takes shape, rendering it delirious (Deleuze), as humanity can be traced in the Barbarian and barbarism can in turn affect humanity beyond the figure of the Thracian. As the act and language of love are turned into linguistic abuse and physical rape, Laurens’ formal experimentations, where language and the Other of language meet at the crossroad of their own contradictions, allow for a renewal in the meaning of the Greek myth as well as in the dramatic language on the British stage at the start of the twenty-first century.